Assembly of BLDC Motor Control Configuration in Electric Aircraft - Muhammad Syamsi; Sugeng Hadi Susilo (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
The movement and stability of a quadcopter is very dependent on the speed of the propellers which are controlled by the BLDC motor. Each propeller produces thrust and torque that is regulated to rotate clockwise (CW) and counter clockwise (CCW). It is important to maintain the balance of the quadcopter, flying electric vehicles such as quadcopters face challenges in the control system, especially in the BLDC motor. Therefore, the program configuration on the quadcopter controller is very important so that the quadcopter can fly stably as desired by controlling the rotation of the BLDC motor and utilizing sensors to support flight stability. DJI NAZA M V2 is a good flight controller in the quadcopter category, mainly because of its advanced control algorithm and stability features. This advantage allows users to have a stable and safe flight even in unfavorable weather conditions. The application of BLDC motor control program configuration to flying electric vehicles, especially quadcopters, shows that the configuration of the flight controller and electronic speed control has a significant impact on overall performance. Configuration includes basic settings such as mixer type, battery, throttle, reverse, timing degree, brake, power, and helicopter mode. The right combination of settings can make the quadcopter operate optimally and stably in various conditions.